(untitled) (Itinera, 2024)
Proust gave metaphor both stylistic and theoretical centrality. In his view, metaphor is not a mere substitute for literal expression but performs a cognitive function, bringing to light relations and aspects of reality that would otherwise remain unexplored. The article intends to show that the reminiscences of involuntary memory also possess a metaphorical structure. Just as a pars destruens and a pars construens coexist in metaphor, in authentic reminiscence the deconstruction of a linear and abstract temporality is the indispensable premise of reconfiguring the past that makes its meaning flash forth in unprecedented possibilities. Like metaphor, involuntary memory must enact categorical transgression. It must suspend previous categories and classifications to bring out the rich web of relationships that permeates every fragment of our existence. Finally, just as metaphor redescribes reality under the banner of metamorphosis, so involuntary memory transforms the usual relationships between past and present. The artwork born from the epiphanies of involuntary memory will adopt an expressive practice capable of interweaving reality and imagination, perception and memory, objectivity, and subjectivity.